Cooperatives and Socio-Economic Empowerment Among Rural Women (Researcher CAB: A Journal for Research and Development, 2024)
This paper discusses the role of cooperative societies in empowering rural women through Nalachhap Pragatisil Women Saving and Credit Cooperatives Limited (NPWSCCL) in Bhaktapur particularly focusing on socio-economic aspects. It also highlights the social and economic challenges faced by rural women, such as limited decision-making power and poor economic conditions. The study uses descriptive research design followed by 55 sample respondents. Data were of both qualitative and quantitative nature collected through survey and interview respectively. The findings indicate a positive change in women's decision-making abilities after joining the cooperative, along with slight improvements in income and expenditure patterns. However, there is a need for skill development training programs for rural women. Overall, the efforts have not only empowered women but also contributed significantly to societal well-being and the promotion of social and economic change within the community but further efforts are needed to provide comprehensive support.